Juegos tradicionales y la motricidad gruesa en niños de la institución educativa inicial N°522 Isabel Sandoval Rodriguez, Caballococha 2024 - Reategui Huaycama, Nara Raquel (2025)
The purpose of this research was to analyze the relationship between traditional game participation and gross motor development in children attending Isabel Sandoval Rodríguez Early Childhood Education Institution No. 522 in Caballococha, during the year 2024. A relational approach with a non-experimental design was adopted. The study population consisted of a total of 68 children enrolled at the institution. Data collection was based on observation, supported by a guide validated by expert judgment. The reliability of the instrument was determined using Cronbach's alpha coefficient based on the results of a pilot test, which allowed for verification of the internal consistency of the items comprising the instrument. The findings showed a positive and statistically significant relationship between participation in traditional games and gross motor development in the children evaluated. With a Spearman's Rho correlation coefficient of 0.745 and a significance level of 0.05, it was determined that children who actively participated in these types of traditional games showed greater mastery in skills such as balance, coordination, strength, and control of their body movements.